Catheter-related bloodstream infection caused by Tsukamurella tyrosinosolvens identified by secA1sequencing in an immunocompromised child: a case report - Shinsuke Mizuno; Yoshiyuki Tsukamura; Shuro Nishio; Toshiaki Ishida; Daiichiro Hasegawa; Yoshiyuki Kosaka; Tadasuke Ooka; Junichiro Nishi; Masashi Kasai (BMC, 2023)
Abstract Background Tsukamurella spp. are obligate aerobic, gram-positive, non-motile, and slightly acid-fast bacilli belonging to the Actinomycetes family. They share many characteristics with Nocardia, Rhodococcus, Gordonia, and the rapidly growing Mycobacterium species. Therefore, standard testing may misidentify Tsukamurella spp. as another species. Accurate and rapid diagnosis is critical for proper infection management, but identification of this bacterium is difficult in the standard laboratory setting. Case presentation A bloodstream infection caused by a gram-positive bacterium and related to a central venous catheter was identified in an immunocompromised 2-year-old girl. Tsukamurella tyrosinosolvens was identified by modified secA1 sequencing. Antibiotic treatment and removal of the central venous catheter resolved the infection. Inappropriate management of the catheter during an overnight stay outside of the hospital was considered as a possible source of infection. Conclusions SecA1 sequencing may be a useful diagnostic tool in the identification of T. tyrosinosolvens. Providing proper central venous catheter care instructions to patients, their families, and medical staff is important for infection prevention.